The Influence of Brand Image, Promotion and Product Availability on Consumer Repurchase Interest of Pepsodent Siwak 150gr Toothpaste Products at Al Zahra Banjarbaru Mini Market - Margareta Setyorini; Setio Utomo; Maryono; Humaidi (Journal of Business Transformation and Strategy, 2025)
Abstract: This study aims to determine and test the partial and simultaneous influence of Brand Image, Promotion and Product Availability on Consumer Repurchase Interest of Pepsodent Siwak Toothpaste 150gr Products at Al Zahra Banjarbaru Mini Market. This research is a quantitative study; the research design is an associative method. Sampling in this study used the accidental sampling technique, so the number of research samples was 65 respondents using the Ferdinand formula. The data used were taken from the questionnaire, data analysis using multiple linear regression analysis. The results of the study showed that 1) Brand Image has an insignificant partial effect on Consumer Repurchase Interest of Pepsodent Siwak Toothpaste150gr Products at Al Zahra Banjarbaru Mini Market. 2) Promotion has a significant partial effect on Consumer Repurchase Interest of Pepsodent Siwak Toothpaste 150gr Products at Al Zahra Banjarbaru Mini Market. 3) Product Availability has a significant partial effect on Consumer Repurchase Interest of Pepsodent Siwak Toothpaste 150gr Products at Al Zahra Banjarbaru Minimarkets. And 4) Brand Image, Promotion and Product Availability have a significant simultaneous effect on Consumer Repurchase Interest of Pepsodent Siwak Toothpaste 150gr Products at Al Zahra Banjarbaru Mini Market.